Hasil Lemparan Pada Olahraga Tolak Peluru - Aris Tangdilian Bato Limbong; Muchamad Ishak; Edi Komarudin (Jurnal Master Penjas & Olahraga, 2021)
The purpose of this study was to determine the relationship between the explosive power of the arm muscles, hip joint flexibility and self-confidence with the results of throwing in shot put. This type of research is descriptive quantitative using correlational methods. The population in this study were all high school / vocational high school students who are members of the athletic extracurricular number shot put in Purwakarta Regency as many as 15 people, using total sampling technique, so the sample is the entire population. The instruments used were, seated medicine ball throws, sit and reach, questionnaires and test results. The results of the research show that: 1) There is a significant relationship between the explosive power of the arm muscles and the results of the shot, and it gives a correlation value of 0.738 or 54.4%. 2) There is a significant relationship between hip joint flexibility and the result of shot put, and gives a correlation value of 0.926 or 85.7%. 3) There is a significant relationship between self-confidence and the results of throwing bullets, and gives a correlation value of 0.865 or 74.8%, 4) There is a significant relationship between arm muscle explosive power, hip joint flexibility and confidence together with the results of throwing bullets, and giving a correlation value of 0.895 or 80.1%.